Armed and Dangerous? UAVs and U.S. Security - Davis, Lynn E. (RAND Corporation, 2014)
Armed drones are making the headlines, especially in their role in targeted killings. RAND researchers examined whether these weapons are transformative, how dangerous their proliferation will be, and whether U.S. use of them can shape a broader set of international norms that discourage their misuse by others.